Sekolah Pagi-Siang: Solusi atau Tantangan Bagi Pembelajaran yang Berkualitas? - Gumilar, Dinda Amelia; Zahra, Fanya Rachma; Rahmadini, Rizqia; Zikri, Shiva Aqila; Pujiyanah, Tri Silviya; Prihantini, Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Learning effectiveness is influenced by a number of factors, including educator competence, material quality, delivery methods, and study time allocation. In particular, study time has a significant impact on students' concentration and motivation, especially in the context of the implementation of the shift system in Indonesia, which divides study time into morning and afternoon sessions. This study aims to illustrate the importance of learning time management and its impact on student motivation, concentration, and learning outcomes. This study uses a literature study approach to analyze the influence of learning time duration and system shifts on learning effectiveness. The main source of data for this research is scientific artifacts published through the Google Scholar database. Data analysis was carried out qualitatively with the knowledge of data reduction, data presentation, and drawing conclusions. The results of the analysis showed that the morning session was more effective in increasing students' concentration and motivation than the afternoon session which tended to cause fatigue. Schools should pay attention to learning time and curriculum adjustments to create a supportive learning environment